The boy in number four - Kootstra, Kara (Dial Books for Young Readers, an imprint of Penguin Group (USA) LLC, 2014)
Young Bobby Orr works hard to be the best hockey player he can be and his efforts pay off in one of the many important games that help prepare him to achieve his dream of one day playing in the big leagues.